Penerapan Hukuman Mati Bagi Pelaku Tindak Pidana Korupsi - Muwahid Muwahid (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Research on the application of the death penalty for perpetrators of corruption is a research library , with the purpose to find out: first, setting the death penalty in law of corruption; secondly, the application of the death penalty for perpetrators of corruption in a human rights perspective. Primary data were obtained from the legislation, secondary data obtained from the criminal law books, law journals, and legal dictionaries. Data was collected to study the document. While the use of data analysis techniques